Food Security As a Human Right In India: Examining the Situation and Obligations for Ensuring Food Security in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Food security is a condition related to the ongoing availability of food. Concernsover food security have existed throughout history. There isevidence of granaries being in years ago , with central authorities inCivilizations including Ancient China and Ancient Egypt being known torelease foodfrom storage in times of famine. Yet it was only at the 1974 World Food Conference that the term 'foodsecurity' was established as a formal concept. Originally, food security was understood to apply at thenational level, with a state being food secure when there was sufficient food to "sustaina steady expansion of food consumption and to offset fluctuations inproduction and prices ".A new definition emerged at 1996 World Food Summit;this time with the emphasis being on individuals enjoyingfood security, rather than the nation . According to theFood and Agriculture Organization (FAO), food security "existswhen all people, at all times, have physical and economic access to sufficient, safeand nutritious food to meet their dietary needs and food preferences for an active andhealthy life ".Over the past decade, a series of events in India have brought the questionof food security into sharp focus. Vast famine-affected areas versus surplusproduction and stocks of grains, the impact of globalization and World TradeOrganization laws on agriculture and farmers, the media’s spotlight onstarvation deaths and, finally, the Supreme Court of India’s strong reaction tothe plight of the hungry—all make a case for recognizing the right to food.Thispaper examines the situation prevailing in India and reviews the obligationsand initiatives by the government of India to ensure food security.